Navigating feedback conference episodes in Polish: Cultivating the self-awareness of tutors - Bąk-Średnicka, Anna (Glottodidactica, 2024)
This study was a (self-)analysis of supervisory discourse of preservice Teaching English to Speakers of Other Languages practicum post-observation feedback conferences (POFCs). This discourse was analysed using the framework of conversation analysis (CA) in five areas that constitute POFCs as a communicative genre. The aim was to identify dialogic elements that constitute supportive, democratic, and open dialogue, which, in turn, fosters the development of the characteristics of a professional and empathetic teacher. The analysis of this corpus revealed that the two tutors’ utterances contained elements of both conversational and institutional styles, and they were dominated by a strategy of anchoring when a practical topic or problem observed in the classroom was a point of reference for introducing a more complex topic. When the tutee was not ready for discussion at this conceptual level, the conversation shifted to what took place during the observed lessons. Emotional support was linguistically realised via face support/tenderness utterances that protected, supported, and provided space for developing self-confidence, personal, and professional identity of the students. This study fits into the debate on the topic of effective and empathic POFCs. The examination of tutors’ own utterances raises their awareness of the language they use with tutees.